Síntese de cerâmicas tipo perovskita com potencial uso em células solares - Nascimento, Cássia Costa (Universidade Federal de São Carlos, 2017)
Visible light accounts for the biggest fraction of the solar irradiance. One of the strategies for achieving higher photovoltaic power conversion efficiency is the application of low band-gap materials (Eg ideal≈1.4 eV) capable of absorbing this fraction of the solar spectrum. Ferroelectric semiconductors have been studied in this field due to the above-bandgap generated photovoltages and their ferroelectric polarization-driven carrier separation. Ferroelectric oxides usually present wide bandgaps which allow the absorption of only 8-20% of the solar spectrum. However, the development of new ferroelectric materials, particularly KBNNO [KNbO3]0,9[BaNi0,5Nb0,5O3-δ ]0,1 (Eg = 1.39 eV) and KBiFe2O5 (Eg=1,60 eV), has encouraged the use of such materials in solar cells. Simple synthesis routes, with short steps, time and temperatures are essential for the future progress of the application of such ferroelectric oxides in solar cells. KBNNO and KBiFe2O5 require high crystallization temperatures, which reduce the number of potential substrates and electrode materials that could be used in devices, as polymer-based flexible ones. Obtaining this oxides in a high surface-area powder form might be a strategy to further incorporation in solar cells composed of low-temperature processing materials. This work reports for the first time synthesis of KBNNO and KBiFe2O5 by solution combustion (SCS). Characterization by WAXD, SEM, EDS, TG/DSC and Diffuse Reflectance UV-Vis Spectroscopy and dielectric constants indicates the success of the synthesis. The optical properties show the visible-light absorption contribution and band-gaps closer to the ideal magnitude for solar applications compared to the non doped materials. The SCS was shown as an effective route to obtaining the phase. Furthermore, it is possible to improve it in order to produce powders with smaller particle size and absent of secondary phases.
Synthesis of perovskite-type ceramics with potential application in solar cells
Keywords: Perovskita; Ferroelétrico; Síntese por combustão em solução; Perovskite; Ferroelectric; Solution combustion synthesis; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA